Microstructural properties of semisolid welded joints for AISI D2 Tool Steel - Mohammed, M.N.; Omar, M.Z.; Syarif, J.; Sajuri, Z.; Salleh, M.S.; Alhawari, K.S. (Fakulti Kejuruteraan ,UKM,Bangi., 2014)
The aim of this study is to investigate experimentally the microstructural evolution of the joints using ledeburitic AISI D2 Tool Steel parts. The application of a new process of the semisolid joining of two parts of AISI D2 cold-work tool steel is proposed using a partial remelting method. Samples were heated in an argon atmosphere up to 1300°C and held for 10 minutes. Metallographic analyses along the joint interface showed a smooth transition from one to the other and neither oxides nor microcracking was observed. The current work successfully confi rmed that avoidance of a dendritic microstructure in the semisolid joined zone and high bonding quality components can be achieved without the need for force or complex equipment when compared to conventional welding processes.